Laserstrahlhartlöten mit Zweistrahltechnik - Hanebuth, Henning (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1996)
The aim of this thesis is to obtain basic knowledge about automated and flux free laser beam brazing of formed sheet metal parts with double beam. The brazing system was composed of two Nd:YAG-lasers, a 6-axis-articulated robot as well as a filler metal and a shielding gas supply. In addition an online process control was developed, based on the detection of the surface temperature. In fundamental investigations of the process the arrangement of the laser beams as well as of the filler metal and the shielding gas supply were optimized. Intensive studies of the joint quality have shown good results concerning wetting and filling degree. Besides small thermal distortion occurred and high strength could be obtained. Applying two laser beam sources allows a controlled and separate in-coupling of the laser beam energy for each part of the joint. Thus different temperature profiles at the joints investigated can be optimal designed through the variation of focal position, angle of beam incidence and the arrangement of the laser beam working spots to the joint or the gap. The laser beam brazing technique presented delivers basic knowledge for the realization in industr